Association of mast cells and bone marrow reticulin fibrosis in patients with bcr-abl negative chronic myeloproliferative neoplasms - Keski, Hakan (Blood cells, molecules, & diseases, 2020)
We aimed to investigate the association of bone marrow mast cell numbers (MCN) and the degree of reticulin fibrosis in patients with chronic myeloproliferative neoplasms (MPN). This was a case-control study that recruited 47 patients who were diagnosed with bcr-abl negative MPN. Thirty patients with lymphoma served as controls. JAK2 mutation was studied and all subjects underwent bone marrow biopsy at the time of diagnosis. Mast and CD34+ cells were counted. Marrow reticulin fiber was graded. Thirty-four patients had essential thrombocythemia (ET), 8 patients had primary myelofibrosis (PMF) and 5 patients had polycythemia vera (PV). Fourteen MPN patients had JAK2, whereas the controls had not. MCN was higher in patients than controls (p = 0.001). There was no significant difference regarding CD34. Reticulin fibrosis was present in 57.4% of MPN patients, whereas there was any in controls. PMF patients had more CD34 + cells than PV and ET. PMF patients had more reticulin fibers compared with other subgroups (p < 0.001). MCN, but not CD34+ cell counts, was significantly higher in JAK2(+) patients than JAK2(−) patients. MCN and reticulin fibrosis were significantly increased in MPN patients. JAK2 positivity had significantly increased MCN compared to patients without JAK2. JAK2 was associated with increased reticulin fibrosis.